2018
DOI: 10.1177/0890334418755689
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Versus Bottle Feeding on Malocclusion in Children: A Meta-Analysis Study

Abstract: Breastfeeding beneficially affects primary occlusion when practiced for at least 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 75 publications
1
15
0
10
Order By: Relevance
“…23 The upshot is impaired oral health-related quality of life. 24 The findings of a previous literature review 25 reinforce the benefits of adopting exclusive breastfeeding practices and avoiding non-nutritive sucking habits to promote harmonic craniofacial growth, with lifelong benefits. In addition, professionals should be aware of the possible consequences of non-nutritive habits, so that they can diagnose and monitor its sequelae, and thus reduce the development of sever malocclusion.…”
Section: Discussionmentioning
confidence: 85%
“…23 The upshot is impaired oral health-related quality of life. 24 The findings of a previous literature review 25 reinforce the benefits of adopting exclusive breastfeeding practices and avoiding non-nutritive sucking habits to promote harmonic craniofacial growth, with lifelong benefits. In addition, professionals should be aware of the possible consequences of non-nutritive habits, so that they can diagnose and monitor its sequelae, and thus reduce the development of sever malocclusion.…”
Section: Discussionmentioning
confidence: 85%
“…The determined criterion for the duration of lactation was less or more than the age of 2 years, based on the researchers' decision. (7) Statistical analysis:…”
Section: Methodsmentioning
confidence: 99%
“…(6) Breastfed children have a sufficiently developed base of the maxillary and mandibular bones in the frontal (anterior-posterior axis), transverse (longitudinal axis), and sagittal (lateral axis) planes, which can property affect the occlusion of deciduous teeth. (7) Some studies have reported breastfeeding as a protective factor against malocclusion and have linked prolongation of breastfeeding with a reduction in the ratio of children with malocclusion requiring orthodontic treatment. (2,3,8,9) Conversely, there are reports on the lack of relationship between the duration of breastfeeding in the first year of birth and occlusal and dental arch parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Não existe um consenso na literatura sobre a oclusão dos rodetes gengivais ao nascimento e a sua influência sobre a futura inter-relação da oclusão da dentadura decídua. Autores de revisões contemporâneas da literatura sobre forma de alimentação e hábitos orais deletérios concluem que o aleitamento materno exclusivo nos seis primeiros meses de vida afeta de forma benéfica a oclusão decídua; ao mesmo tempo, citam como exemplo de influência negativa ao crescimento orofacial os hábitos orais deletérios, como o uso de mamadeira, a sucção digital e o predomínio da respiração oral, causando oclusopatias e alterações na relação entre a maxila e a mandíbula, evidenciando a ação do ambiente influenciando a genética (epigenética) no que se diz respeito ao crescimento e desenvolvimento oral 88,89,90,91,92,93 . Com relação especificamente às crianças nascidas prematuras, a literatura mostra a possibilidade da observação de um número elevado de crianças portadoras de oclusopatias com necessidade de tratamento ortodôntico, assim como uma morfologia craniofacial alterada em crianças nascidas prematuras quando comparadas a crianças nascidas a termo 94,95,96 .…”
Section: Cavidade Oral Edêntula E Os Tipos De Oclusão Entre Os Rodeteunclassified